Cabaran penyeragaman undang-undang jenayah syariah di Malaysia - Zaini Nasohah,; Zurul Iman Zakaria,; Zuliza Mohd Kusrin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sharia Criminal law has long been implemented in every state in Malaysia. However, the implementation of the law often receives negative perceptions and views from the society. One of the issues raised regarding the shariah criminal law is that the law is not standardize and is varied among the states. This difference may cause injustice to the accused those involved in a sharia criminal offences. A significant difference can be seen from the aspects of types and categories of offences, texts, nature and level of punishment even though it refers to the same offence. Efforts towards the standardization of sharia criminal law has long been sought, but has yet to be materialised due to some issues and challenges faced by the Department of Islamic Development Malaysia (JAKIM), an agency which is responsible to coordinate and standardise the sharia law in Malaysia. This article aims to analyse the challenges face in the effort to uniform the sharia criminal law in Malaysia. This study is a qualitative study which utilises documents analysis approach in its data collection process. The study found that there are three major challenges to uniform the sharia criminal law in Malaysia which include the jurisdiction, politics and social. Therefore, further studies should be undertaken to assist the religious authorities in finding the best method to address these issues and challenges in order to standardize the sharia criminal law in Malaysia.